To Be Both (and More): Immigration and Identity Multiplicity. (26th April 2019) - Verkuyten, Maykel; Wiley, Shaun; Deaux, Kay; Fleischmann, Fenella
Abstract: Immigrants and their descendants make up a growing share of the population in countries across Europe, North America, and Oceania. This large‐scale immigration challenges once relatively stable notions of ethnic, national (or regional), and religious identities. Immigrants and their children confront the task of defining themselves in a new and unfamiliar context. Questions regarding immigrants' identifications with their ethnic and national groups—but also with local, religious, and supranational groups—have animated national policy debates. This special issue brings together research on migrants' sense of a "being both, " and the research and policy implications of this particular form of multiple identification. This introductory article discusses the conceptualisation of multiple identification, the importance of group dynamics for the adoption of dual identities, as well as the implications of identification with multiple social groups for immigrants and their receiving societies.